Optimizing Potato Value Chains for SDG2: Evidence from Farmer-level Economics and Marketing Strategies - Anisha Sil; Mrittika Das; Soumik Ray; Achal Lama; Ajeet J. Williams; Pradip Kumar Sahu (Potato Research, 2026)

Geometric morphometrics enables accurate predictions of palaeoecology and reveals unique adaptations to an expanded niche space in extinct waterfowl - Ray Mariano Chatterji; Shante Williams; Janet C. Buckner (Evolutionary Ecology, 2026)

Challenges and Opportunities for Strengthening Bottom‐Tow Fisheries Sustainability - Suresh A. Sethi; Robert D. Murphy; Matthew R. Baker; Anita C. Kroska; Haraldur A. Einarsson; Owen S. Hamel; Shelton J. Harley; Pingguo He; James Ianelli; Stan Kotwicki; Robert A. McConnaughey; Chris McGonigle; et al. (Fish and Fisheries, 2026)
Bottom‐tow gear fisheries (trawls and dredges) produce ~24 million mt of harvest annually, representing a globally important animal‐sourced food system. While many are currently sustainably managed, growing concern over the potential for ecosystem impacts from bottom‐tow gears has increased pressure to improve these fisheries. We assembled an international working group of > 30 contributors, including fishing industry participants, managers, non‐governmental ocean conservation organization representatives, and scientists to synthesize obstacles to bottom‐tow fisheries sustainability and to develop expert‐based recommendations to operationalize sustainability advancements moving forward. We identified 30 key gaps impeding bottom‐towed fisheries sustainability spanning 6 core challenge areas including: seafloor disturbance, bycatch and discards, management design and implementation, fishing operations, cross‐sector conflicts, and public perception and communication. We generated 28 priority recommendations to address bottom‐tow fisheries sustainability obstacles with themes including: addressing data gaps, advancing mechanistic understanding and modelling tools, strengthening management processes, and improving knowledge sharing and communication. Cross‐disciplinary and diverse system experience among fisheries and marine ecosystem stakeholders will be critical for operationalizing bottom‐tow fisheries sustainability advancements. As the global human population approaches 10 bn in the next 30 years, ensuring sustainable wild capture fisheries is an imperative for feeding the world. Outputs from this synthesis serve as a resource for fishing and marine ecosystem stakeholders to identify key challenge areas and associated entry points for solutions‐oriented efforts to improve the sustainability of bottom‐tow fisheries.

Complex eruption processes and deposits of basaltic fissures: insights from the ~37 ka Budj Bim volcanic complex, Southeastern Australia - Janine L. Kavanagh; Katy J. Chamberlain; Jade A. Hrintchuk; Elisabetta Mariani; Julie Boyce; Stefano Urbani; Tegan A. Havard; Kate M. Williams; Ray A. F. Cas (Bulletin of Volcanology, 2026)
Throughout Earth’s history, eruptions from volcanic fissures have been responsible for some of the largest outpourings of basaltic magma, impacting climate and society. In continental monogenetic settings, these eruptions can occur on short timescales and with short notice after long quiescence. Their deposits are often quickly destroyed or buried as the eruption progresses, limiting understanding of eruption triggers and hazards uniquely garnered from these tephra layers and lavas. The ~37 ka Budj Bim Volcanic Complex (BBVC) in the active intracontinental monogenetic Newer Volcanics Province (NVP), southeastern Australia (~4.5 Ma to present), is a rarely preserved volcanic fissure system that provides new insight on how magma ascent dynamics impact eruptions. The BBVC comprises a 2.2 km long array of basaltic scoria cones, spatter cones, an elongate open crater with steep inward-sloping walls and a substantial lava-tube-fed flow field. Newly logged eruption sequences, petrography and geochemical analysis reveal five eruption stages, involving vent-shifting along a dyke-fed fissure, and rapid changes in eruption styles between Strombolian and micro-Plinian activity interspersed with concurrent and intermittent phreatomagmatism. The eruption culminated in the establishment and then breach of an elongate lava lake, feeding the > 30 km long culturally significant Tyrendarra lava flow (UNESCO World Heritage site). The BBVC eruption would have evolved similarly to the 2014–2015 Bárðarbunga-Holuhraun fissure eruption in Iceland, but with increased complexity due to its intraplate continental setting and feeder dyke interaction with aquifers and near-surface faults, resulting in greater level of phreatomagmatism and explosion depths potentially down to 320 m. This finding must be considered to improve future eruption scenario assessments in the NVP and builds new understanding of complex volcanic fissure eruption behaviour that can be applied to similar systems around the world.

Evaluating surface fluxes in WRF using eddy-covariance flux measurements in the Western and Eastern U.S. - Fan Wu; Kenneth J. Davis; Li Zhang; Ray G. Anderson; Jason P. Horne; Sarah Goslee; William Munger; Chenxia Cai; Yu Yan Cui; Zhan Zhao; Min Zhong (Agricultural and Forest Meteorology, 2026)

Expert perspectives on exposure-response functions for urban health policy: Lessons from a UBDPolicy workshop - Harry Williams; Zorana Jovanovic Andersen; Hanna Boogaard; Søren Brage; Matthew H.E.M. Browning; Samuel Cai; Xuan Chen; Priyanka deSouza; Angel M. Dzhambov; Benjamin Fenech; Gillian Flower; Francesco Forastiere; et al. (Environmental Research, 2026)

Manistee, a new Round-White Early to Mid-Season Maturing Potato Variety with Excellent Long-Term Storage Potential - David S. Douches; Joseph J. Coombs; William L. Behling; Ray Hammerschmidt; Greg E. Steere; Matthew L. Zuehlke; Christopher M. Long (American Journal of Potato Research, 2025)
Manistee is a round white chip-processing potato ( Solanum tuberosum ) variety developed for long-term storage. Evaluated as MSL292-A, Manistee is a selection from a cross between Snowden and the chip-processing breeding line MSH098-2. The tubers of Manistee are compressed, round with shallow eyes and early to mid-season maturity. Field testing and on-farm trials show that this variety has high yield potential with specific gravity comparable to Snowden and similar to better tolerance to blackspot bruise. Manistee was formally released in 2013 and has demonstrated reliable and excellent long-term storage chip-processing quality up to eight months post-harvest which extends the chip-processing storage season beyond Snowden. Furthermore, preliminary studies with Manistee, Snowden, Lamoka and Pike tuber disks demonstrated that Manistee started the wound healing process faster than Lamoka and Pike and slightly faster than Snowden which supports observations of stable and reliable commercial storage of the tubers for chip-processing.

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Efficacy of unbaited and baited green multi-funnel traps for detection of Agrilus species and other wood-boring beetle taxa - Giacomo Santoiemma; Jon Sweeney; Everett G. Booth; Giacomo Cavaletto; Gianfranco Curletti; Sarah M. Devine; Joseph A. Francese; Emily K. L. Franzen; Filippo Giannone; Mischa Giasson; Jerzy M. Gutowski; Cory Hughes; et al. (Journal of Pest Science, 2025)
Semiochemical-baited traps are a key component of post-border surveillance for detection of non-native and potentially invasive bark and wood-boring beetles (Buprestidae, Cerambycidae, Curculionidae: Scolytinae) at risk of introduction in untreated woody materials used in global trade. Because the particular species that may arrive with imported goods is unknown, plant protection agencies need trapping protocols that effectively survey all three taxa. Baiting traps with host volatiles and aggregation/sex pheromones of longhorn beetles increases efficacy of detecting Cerambycidae and Scolytinae, but its effect on detection of Agrilus species and other jewel beetles is unknown. In this multi-country trapping study we found that the addition of ethanol and common aggregation/sex pheromones of longhorn beetles to green multi-funnel traps placed in the mid-upper forest canopy had negative effects on abundance of Agrilus species and other jewel beetles collected but no effect on their species richness, and significant positive effects on species richness and abundance of Cerambycidae and Scolytinae. Baiting green canopy traps with longhorn beetle pheromones increased the efficacy of traps for detecting total target taxa of bark and wood-boring beetles at risk of international movement in untreated woody materials. This information is beneficial for the design of multi-taxa surveys, potentially saving money and resources without decreasing trapping efficacy.

Graphene-coated sand for enhanced water reuse: Impact on water quality and chemicals of emerging concern - Abdulla Nusair; Madelyn Barber; Avijit Pramanik; Cheyenne Ethridge; Clinton William; Hunain Alkhateb; Mine Ucak-Astarlioglu; Paresh Chandra Ray; Matteo D'Alessio (Science of The Total Environment, 2024)

Trends in Arctic-nesting loon (Gavia spp.) populations in North America - Ingrid L. Pollet; Sarah E. Gutowsky; Ray T. Alisauskas; William Harvey; Dana K. Kellett; Kristen M. Lalla; Josée Lefebvre; Jake Russell-Mercier; Jennifer F. Provencher; Emily D. Silverman; Paul A. Smith; Mark L. Mallory (Polar Biology, 2024)

Efficacy of trapping protocols for Agrilus jewel beetles: a multi-country assessment - Giacomo Santoiemma; David Williams; Everett G. Booth; Giacomo Cavaletto; James Connell; Gianfranco Curletti; Maarten de Groot; Sarah M. Devine; Abigail Enston; Joseph A. Francese; Emily K. L. Franzen; Mischa Giasson; et al. (Journal of Pest Science, 2024)
The genus Agrilus is one of the most diverse insect genera worldwide. The larval feeding activity causes extensive damage in both forests and orchards. In addition, more than 30 species have been introduced outside their native range so far, including the emerald ash borer Agrilus planipennis Fairmaire. Thus, the availability of efficient trapping protocols for early detection of Agrilus species at entry points is of utmost importance. In this study we tested whether trapping protocols developed for surveillance of A. planipennis in North America were also effective for other Agrilus species. In particular, through a multi-country assessment we compared the efficacy of detecting Agrilus species on: (i) green glue-coated prism traps vs. green Fluon-coated multi-funnel traps when baited with the green leaf volatile ( Z )-3-hexenol or left unbaited; and (ii) green multi-panel traps vs. green multi-panel traps baited with dead adult Agrilus beetles (decoys). A total of 23,481 individuals from 45 Agrilus species were caught. Trap design significantly affected both species richness and abundance of Agrilus species in several of the countries where the trapping experiments were carried out, and green prism traps outperformed green multi-funnel traps in most cases. On the contrary, the addition of a ( Z )-3-hexenol lure or dead adult beetle decoys on to traps did not improve trap catches. Our study highlights that reliable trap models to survey Agrilus species are already available, but also that there is the clear need to further investigate chemical ecology of Agrilus species to develop semiochemical lures that can improve detection efficacy.

Metagenomics untangles potential adaptations of Antarctic endolithic bacteria at the fringe of habitability - Claudia Coleine; Davide Albanese; Angelique E. Ray; Manuel Delgado-Baquerizo; Jason E. Stajich; Timothy J. Williams; Stefano Larsen; Susannah Tringe; Christa Pennacchio; Belinda C. Ferrari; Claudio Donati; Laura Selbmann (Science of The Total Environment, 2024)

Quota use in mixed‐stock fisheries - William A. Karp; Michael C. Melnychuk; Robyn E. Forrest; Lorne Richard Little; Kristin McQuaw; Chad Demarest; Ray Hilborn; Nicole Baker; Brian Mose; Bruce Turris; Ernesto Penas Lado (Fish and Fisheries, 2024)
Although most fisheries assessment and management focuses on the status of individual stocks, and regulations are commonly established as single‐species total allowable catch limits (TACs), much of the catch from global fisheries comes from mixed‐stock fisheries where species cannot be harvested separately. We show that in some fisheries where TAC and catch of demersal fish stocks are tracked, the average fraction of TAC harvested ranges from 21% to 68% overall and is declining. This is, in part, related to efforts to protect all species from overfishing, leading to ‘choke species’, which limit fishing pressure on other target species. While some choke species arise from a mix of low and high‐productivity species, others result from allocation processes, which can be aggravated by shifting distributions due to climate change. Underutilization of TACs can also result from market limitations, low value of individual species, undercapacity or management measures. Proposed methods for increasing long‐term yield require species to be managed in stock groups, or allowing the abundance of some stocks to fall below target reference points. We suggest that the observed low and declining aggregate harvests are due, primarily, to the focus on single‐stock sustainability measures, rather than performance of the fisheries in relation to potential overall yield. While there is a growing consensus that single‐species management should be replaced by an ecosystem‐based approach, this will require clear legislative directives regarding management of the trade‐offs involved. Time series considered in this analysis do not extend beyond 2019.

Cytoskeletal Remodeling and Gap Junction Translocation Mediates Blood–Brain Barrier Disruption by Non-invasive Low-Voltage Pulsed Electric Fields - Neeraj Raghuraman Rajagopalan; William-Ray Vista; Masashi Fujimori; Laurien G. P. H. Vroomen; Juan M. Jiménez; Niranjan Khadka; Marom Bikson; Govindarajan Srimathveeravalli (Annals of Biomedical Engineering, 2024)

Assessing parallel path cooling tower performance via artificial neural networks - Christopher Katinas; Brian d'Entremont; William Ray; Michael Willis; Thomas Reichardt (Annals of Nuclear Energy, 2023)

A pilot study investigating feasibility of mainstreaming germline BRCA1 and BRCA2 testing in high-risk patients with breast and/or ovarian cancer in three tertiary Cancer Centres in Ireland - Terri Patricia McVeigh; Karl J. Sweeney; Donal J. Brennan; Una M. McVeigh; Simon Ward; Ann Strydom; Sheila Seal; Katherine Astbury; Paul Donnellan; Joanne Higgins; Maccon Keane; Michael J. Kerin; et al. (Familial Cancer, 2023)

An indolizine squaraine-based water-soluble NIR dye for fluorescence imaging of multidrug-resistant bacteria and antibacterial/antibiofilm activity using the photothermal effect - Sanjay Singh; William E. Meador; Avijit Pramanik; Paresh Ray; Jared H. Delcamp; Yongfeng Zhao (Journal of Photochemistry and Photobiology B: Biology, 2023)

The role of adaptive capacity in incremental and transformative adaptation in three large U.S. Urban water systems - Lisa Dilling; Meaghan E. Daly; William R. Travis; Andrea J. Ray; Olga V. Wilhelmi (Global Environmental Change, 2023)

Bridge to the future: Important lessons from 20 years of ecosystem observations made by the OzFlux network - Jason Beringer; Caitlin E. Moore; Jamie Cleverly; David I. Campbell; Helen Cleugh; Martin G. De Kauwe; Miko U. F. Kirschbaum; Anne Griebel; Sam Grover; Alfredo Huete; Lindsay B. Hutley; Johannes Laubach; et al. (Global Change Biology, 2022)
In 2020, the Australian and New Zealand flux research and monitoring network, OzFlux, celebrated its 20 th anniversary by reflecting on the lessons learned through two decades of ecosystem studies on global change biology. OzFlux is a network not only for ecosystem researchers, but also for those ‘next users’ of the knowledge, information and data that such networks provide. Here, we focus on eight lessons across topics of climate change and variability, disturbance and resilience, drought and heat stress and synergies with remote sensing and modelling. In distilling the key lessons learned, we also identify where further research is needed to fill knowledge gaps and improve the utility and relevance of the outputs from OzFlux. Extreme climate variability across Australia and New Zealand (droughts and flooding rains) provides a natural laboratory for a global understanding of ecosystems in this time of accelerating climate change. As evidence of worsening global fire risk emerges, the natural ability of these ecosystems to recover from disturbances, such as fire and cyclones, provides lessons on adaptation and resilience to disturbance. Drought and heatwaves are common occurrences across large parts of the region and can tip an ecosystem's carbon budget from a net CO 2 sink to a net CO 2 source. Despite such responses to stress, ecosystems at OzFlux sites show their resilience to climate variability by rapidly pivoting back to a strong carbon sink upon the return of favourable conditions. Located in under‐represented areas, OzFlux data have the potential for reducing uncertainties in global remote sensing products, and these data provide several opportunities to develop new theories and improve our ecosystem models. The accumulated impacts of these lessons over the last 20 years highlights the value of long‐term flux observations for natural and managed systems. A future vision for OzFlux includes ongoing and newly developed synergies with ecophysiologists, ecologists, geologists, remote sensors and modellers.

Identification of structural variation and polymorphisms of a sex co-segregating scaffold in spinach - Li’ang Yu; Xiaokai Ma; William Wadlington; Ray Ming (Plant Reproduction, 2022)

Perturbed ER homeostasis by IGF-IIRα promotes cardiac damage under stresses - Sudhir Pandey; Chia-Hua Kuo; William Shao-Tsu Chen; Yu-Lan Yeh; Wei-Wen Kuo; Ray-Jade Chen; Cecilia Hsuan Day; Pei-Ying Pai; Tsung-Jung Ho; Chih-Yang Huang (Molecular and Cellular Biochemistry, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Evaluating Connections Between Nitrogen Cycling and the Macrofauna in Native Oyster Beds in a New England Estuary - S. G. Ayvazian; Nicholas E. Ray; Anna Gerber-Williams; Sinead Grabbert; Adam Pimenta; Boze Hancock; Donald Cobb; Charles Strobel; R. W. Fulweiler (Estuaries and Coasts, 2022)

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Persistence and resistance: survival mechanisms of Candidatus Dormibacterota from nutrient‐poor Antarctic soils - Kate Montgomery; Timothy J. Williams; Merryn Brettle; Jonathan F. Berengut; Angelique E. Ray; Eden Zhang; Julian Zaugg; Philip Hugenholtz; Belinda C. Ferrari (Environmental Microbiology, 2021)
Summary Candidatus Dormibacterota is an uncultured bacterial phylum found predominantly in soil that is present in high abundances within cold desert soils. Here, we interrogate nine metagenome‐assembled genomes ( MAGs ), including six new MAGs derived from soil metagenomes obtained from two eastern Antarctic sites. Phylogenomic and taxonomic analyses revealed these MAGs represent four genera and five species, representing two order‐level clades within Ca . Dormibacterota. Metabolic reconstructions of these MAGs revealed the potential for aerobic metabolism, and versatile adaptations enabling persistence in the ‘extreme’ Antarctic environment. Primary amongst these adaptations were abilities to scavenge atmospheric H 2 and CO as energy sources, as well as using the energy derived from H 2 oxidation to fix atmospheric CO 2 via the Calvin–Bassham–Benson cycle, using a RuBisCO type IE . We propose that these allow Ca . Dormibacterota to persist using H 2 oxidation and grow using atmospheric chemosynthesis in terrestrial Antarctica. Fluorescence in situ hybridization revealed Ca . Dormibacterota to be coccoid cells, 0.3–1.4 μm in diameter, with some cells exhibiting the potential for a symbiotic or syntrophic lifestyle.

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Serological testing for infectious diseases markers of donor specimens from 24 h after death show no significant change in outcomes from other specimens - Chee Choy Kok; Vidiya Ramachandran; Ece Egilmezer; Sanghamitra Ray; Gregory J. Walker; William D. Rawlinson (Cell and Tissue Banking, 2020)

Asymmetry in Herbivore Effector Responses: Caterpillar Frass Effectors Reduce Performance of a Subsequent Herbivore - Swayamjit Ray; Anjel M. Helms; Nina L. Matulis; Elizabeth Davidson-Lowe; William Grisales; Jared G. Ali (Journal of Chemical Ecology, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Grading Herbaceous Biomass for Biorefineries: a Case Study Based on Chemical Composition and Biochemical Conversion - Amber Hoover; Rachel Emerson; C. Luke Williams; M. M. Ramirez-Corredores; Allison Ray; Kastli Schaller; Sergio Hernandez; Chenlin Li; Michelle Walton (BioEnergy Research, 2019)

Towards Comprehensive Observing and Modeling Systems for Monitoring and Predicting Regional to Coastal Sea Level - Rui M. Ponte; Mark Carson; Mauro Cirano; Catia M. Domingues; Svetlana Jevrejeva; Marta Marcos; Gary Mitchum; R. S. W. van de Wal; Philip L. Woodworth; Michaël Ablain; Fabrice Ardhuin; Valérie Ballu; et al. (Frontiers in Marine Science, 2019)

Patient-Specific Multi-Scale Model Analysis of Hemodynamics Following the Hybrid Norwood Procedure for Hypoplastic Left Heart Syndrome: Effects of Reverse Blalock–Taussig Shunt Diameter - Andres Ceballos; Ray Prather; Eduardo Divo; Alain J. Kassab; William M. DeCampli (Cardiovascular Engineering and Technology, 2019)

Development of an X-specific marker and identification of YY individuals in spinach - William H. Wadlington; Ray Ming (Theoretical and Applied Genetics, 2018)

Association mapping identifies loci for canopy temperature under drought in diverse soybean genotypes - Avjinder S. Kaler; Jeffery D. Ray; William T. Schapaugh; Antonio R. Asebedo; C. Andy King; E. E. Gbur; Larry C. Purcell (Euphytica, 2018)

Computational Investigation of a Self-Powered Fontan Circulation - Marcus W. Ni; Ray O. Prather; Giovanna Rodriguez; Rachel Quinn; Eduardo Divo; Mark Fogel; Alain J. Kassab; William M. DeCampli (Cardiovascular Engineering and Technology, 2018)

Experimental Evaluation of Preservation Techniques for Benzene, Toluene, Ethylbenzene, and Total Xylenes in Water Samples - Ray Arnold; Deyuan Kong; Gregory Douglas; Jeffery Hardenstine; Shahrokh Rouhani; William Gala (Bulletin of Environmental Contamination and Toxicology, 2018)

Genome-wide association mapping of canopy wilting in diverse soybean genotypes - Avjinder S. Kaler; Jeffery D. Ray; William T. Schapaugh; C. Andy King; Larry C. Purcell (Theoretical and Applied Genetics, 2017)

Effects of soil moisture depletion on vegetable crop uptake of pharmaceuticals and personal care products (PPCPs) - Sergio Santiago; Deborah M. Roll; Chittaranjan Ray; Clinton Williams; Philip Moravcik; Allan Knopf (Environmental Science and Pollution Research, 2016)

Prioritization of knowledge‐needs to achieve best practices for bottom trawling in relation to seabed habitats - Michel J Kaiser; Ray Hilborn; Simon Jennings; Ricky Amaroso; Michael Andersen; Kris Balliet; Eric Barratt; Odd A Bergstad; Stephen Bishop; Jodi L Bostrom; Catherine Boyd; Eduardo A Bruce; et al. (Fish and Fisheries, 2016)
Management and technical approaches that achieve a sustainable level of fish production while at the same time minimizing or limiting the wider ecological effects caused through fishing gear contact with the seabed might be considered to be ‘best practice’. To identify future knowledge‐needs that would help to support a transition towards the adoption of best practices for trawling, a prioritization exercise was undertaken with a group of 39 practitioners from the seafood industry and management, and 13 research scientists who have an active research interest in bottom‐trawl and dredge fisheries. A list of 108 knowledge‐needs related to trawl and dredge fisheries was developed in conjunction with an ‘expert task force’. The long list was further refined through a three stage process of voting and scoring, including discussions of each knowledge‐need. The top 25 knowledge‐needs are presented, as scored separately by practitioners and scientists. There was considerable consistency in the priorities identified by these two groups. The top priority knowledge‐need to improve current understanding on the distribution and extent of different habitat types also reinforced the concomitant need for the provision and access to data on the spatial and temporal distribution of all forms of towed bottom‐fishing activities. Many of the other top 25 knowledge‐needs concerned the evaluation of different management approaches or implementation of different fishing practices, particularly those that explore trade‐offs between effects of bottom trawling on biodiversity and ecosystem services and the benefits of fish production as food.

Genome-wide association of familial prostate cancer cases identifies evidence for a rare segregating haplotype at 8q24.21 - Craig C. Teerlink; Daniel Leongamornlert; Tokhir Dadaev; Alun Thomas; James Farnham; Robert A. Stephenson; Shaun Riska; Shannon K. McDonnell; Daniel J. Schaid; William J. Catalona; S. Lilly Zheng; Kathleen A. Cooney; et al. (Human Genetics, 2016)

Habitat availability and gene flow influence diverging local population trajectories under scenarios of climate change: a place‐based approach - Donelle Schwalm; Clinton W. Epps; Thomas J. Rodhouse; William B. Monahan; Jessica A. Castillo; Chris Ray; Mackenzie R. Jeffress (Global Change Biology, 2016)
Ecological niche theory holds that species distributions are shaped by a large and complex suite of interacting factors. Species distribution models ( SDM s) are increasingly used to describe species’ niches and predict the effects of future environmental change, including climate change. Currently, SDM s often fail to capture the complexity of species’ niches, resulting in predictions that are generally limited to climate‐occupancy interactions. Here, we explore the potential impact of climate change on the American pika using a replicated place‐based approach that incorporates climate, gene flow, habitat configuration, and microhabitat complexity into SDM s. Using contemporary presence–absence data from occupancy surveys, genetic data to infer connectivity between habitat patches, and 21 environmental niche variables, we built separate SDM s for pika populations inhabiting eight US National Park Service units representing the habitat and climatic breadth of the species across the western United States. We then predicted occurrence probability under current (1981–2010) and three future time periods (out to 2100). Occurrence probabilities and the relative importance of predictor variables varied widely among study areas, revealing important local‐scale differences in the realized niche of the American pika. This variation resulted in diverse and – in some cases – highly divergent future potential occupancy patterns for pikas, ranging from complete extirpation in some study areas to stable occupancy patterns in others. Habitat composition and connectivity, which are rarely incorporated in SDM projections, were influential in predicting pika occupancy in all study areas and frequently outranked climate variables. Our findings illustrate the importance of a place‐based approach to species distribution modeling that includes fine‐scale factors when assessing current and future climate impacts on species’ distributions, especially when predictions are intended to manage and conserve species of concern within individual protected areas.

Confirmation of delayed canopy wilting QTLs from multiple soybean mapping populations - Sadal Hwang; C. Andy King; Jeffery D. Ray; Perry B. Cregan; Pengyin Chen; Thomas E. Carter; Zenglu Li; Hussein Abdel-Haleem; Kevin W. Matson; William Schapaugh; Larry C. Purcell (Theoretical and Applied Genetics, 2015)

Peter B. Best (1939–2015) - John Bannister; Ken Findlay; Robert L. Brownell; Doug Butterworth; Martin Cawthorn; Greg Donovan; Ray Gambell; Hidehiro Kato; Bruce Mate; Michael Moore; Seiji Ohsumi; William Perrin; et al. (Marine Mammal Science, 2015)

Comparison of low-carbon pathways for California - Geoffrey M. Morrison; Sonia Yeh; Anthony R. Eggert; Christopher Yang; James H. Nelson; Jeffery B. Greenblatt; Raphael Isaac; Mark Z. Jacobson; Josiah Johnston; Daniel M. Kammen; Ana Mileva; Jack Moore; et al. (Climatic Change, 2015)

Coupled Thermal Conductivity Dryout Curve and Soil–Water Characteristic Curve in Modeling of Shallow Horizontal Geothermal Ground Loops - Ray Wu; James M. Tinjum; William J. Likos (Geotechnical and Geological Engineering, 2015)

Colonization of Solidago altissima by the Specialist Aphid Uroleucon nigrotuberculatum: Effects of Genetic Identity and Leaf Chemistry - Ray S. Williams; Megan A. Avakian (Journal of Chemical Ecology, 2015)

Children’s head movements and postural stability as a function of task - Ian Flatters; Faisal Mushtaq; Liam J. B. Hill; Anna Rossiter; Kate Jarrett-Peet; Pete Culmer; Ray Holt; Richard M. Wilkie; Mark Mon-Williams (Experimental Brain Research, 2014)

Facilitating Return to Work for Injured and Ill Animal Agriculture Workers - Iris Anne Reyes; Nancy Bellendorf; Tami Meehan; Ron Wenger; Christopher Kadolph; Shaun Halstead; Andrea Mahnke; Bryan Weichelt; William Ray; Matthew Keifer (Journal of Agromedicine, 2014)

Association analysis of 9,560 prostate cancer cases from the International Consortium of Prostate Cancer Genetics confirms the role of reported prostate cancer associated SNPs for familial disease - Craig C. Teerlink; Stephen N. Thibodeau; Shannon K. McDonnell; Daniel J. Schaid; Antje Rinckleb; Christiane Maier; Walther Vogel; Geraldine Cancel-Tassin; Christophe Egrot; Olivier Cussenot; William D. Foulkes; Graham G. Giles; et al. (Human Genetics, 2014)

The muscarinic M1 receptor positive allosteric modulator PQCA improves cognitive measures in rat, cynomolgus macaque, and rhesus macaque - Jason M. Uslaner; Donnie Eddins; Vanita Puri; Christopher E. Cannon; Jane Sutcliffe; Chan Sing Chew; Michelle Pearson; Jeffrey A. Vivian; Ronald K. Chang; William J. Ray; Scott D. Kuduk; Marion Wittmann (Psychopharmacology, 2013)

Validation of prostate cancer risk-related loci identified from genome-wide association studies using family-based association analysis: evidence from the International Consortium for Prostate Cancer Genetics (ICPCG) - Guangfu Jin; Lingyi Lu; Kathleen A. Cooney; Anna M. Ray; Kimberly A. Zuhlke; Ethan M. Lange; Lisa A. Cannon-Albright; Nicola J. Camp; Craig C. Teerlink; Liesel M. FitzGerald; Janet L. Stanford; Kathleen E. Wiley; et al. (Human Genetics, 2012)

A Benchmark Test for Ecohydrological Models of Interannual Variability of NDVI in Semi-arid Tropical Grasslands - Philippe Choler; William Sea; Ray Leuning (Ecosystems, 2011)

Elevated air temperature alters an old‐field insect community in a multifactor climate change experiment - SHAWN N. VILLALPANDO; RAY S. WILLIAMS; RICHARD J. NORBY (Global Change Biology, 2009)
To address how multiple, interacting climate drivers may affect plant–insect community associations, we sampled insects that naturally colonized a constructed old‐field plant community grown for over 2 years under simultaneous CO 2 , temperature, and water manipulation. Insects were sampled using a combination of sticky traps and vacuum sampling, identified to morphospecies and the insect community with respect to abundance, richness, and evenness quantified. Individuals were assigned to four broad feeding guilds in order to examine potential trophic level effects. Although there were occasional effects of CO 2 and water treatment, the effects of warming on the insect community were large and consistent. Warming significantly increased Order Thysanoptera abundance and reduced overall morphospecies richness and evenness. Nonmetric multidimensional scaling found that only temperature affected insect community composition, while a Sørensen similarity index showed less correspondence in the insect community between temperature treatments compared with CO 2 or soil water treatments. Within the herbivore guild, elevated temperature significantly reduced richness and evenness. Corresponding reductions of diversity measures at higher trophic levels (i.e. parasitoids), along with the finding that herbivore richness was a significant predictor of parasitoid richness, suggest trophic‐level effects within the insect community. When the most abundant species were considered in temperature treatments, a small number of species increased in abundance at elevated temperature, while others declined compared with ambient temperature. Effects of temperature in the dominant insects demonstrated that treatment effects were limited to a relatively small number of morphospecies. Observed effects of elevated CO 2 concentration on whole‐community foliar N concentration did not result in any effect on herbivores, which are probably the most susceptible guild to changes in plant nutritional quality. These results demonstrate that climatic warming may alter certain insect communities via effects on insect species most responsive to a higher temperature, contributing to a change in community structure.

Global GPS data analysis at the National Geodetic Survey - William G. Kass; Robert L. Dulaney; Jake Griffiths; Stephen Hilla; Jim Ray; James Rohde (Journal of Geodesy, 2009)

Mitigating Climate Change with Managed Forests: Balancing Expectations, Opportunity, and Risk - David G. Ray; Robert S. Seymour; Neal A. Scott; William S. Keeton (Journal of Forestry, 2009)

Mercury Concentrations in Fish from Lake Meredith, Texas: Implications for the Issuance of Fish Consumption Advisories - William C. Mcclain; Matthew M. Chumchal; Ray W. Drenner; Leo W. Newland (Environmental Monitoring and Assessment, 2006)

Do geese fully develop brood patches? A histological analysis of lesser snow geese (Chen caerulescens caerulescens) and Ross’s geese (C. rossii) - Jón Einar Jónsson; Alan D. Afton; Dominique G. Homberger; William G. Henk; Ray T. Alisauskas (Journal of Comparative Physiology B, 2006)

Satellite observation of Keppel Islands (Great Barrier Reef) 2002 coral bleaching using IKONOS data - Christopher D. Elvidge; John B. Dietz; Ray Berkelmans; Serge Andréfouët; William Skirving; Alan E. Strong; Benjamin T. Tuttle (Coral Reefs, 2004)

Phytolith morphology and biogenic silica concentrations and abundance in leaves of Chionochloa (Danthonieae) and Festuca (Poeae) in New Zealand - Ray Marx; Daphne E. Lee; Kelvin M. Lloyd; William G. Lee (New Zealand Journal of Botany, 2004)
Biogenic silica concentrations and phytolith morphology and abundance in green leaf material are described in 34 species/subspecies of Chionochloa (Danthonieae) and nine species/subspecies of Festuca (Poeae). A dry‐ash technique was used to extract biogenic silica from mature leaves from plants grown in potting mix. Phytolith morphology and abundance were characterised by scanning electron microscopy and light microscopy, respectively. Biogenic silica concentrations were lowest ( Chionochloa bromoides, C. rubra ssp. occulta, and Festuca multinodis and reached levels of c. 7% in Chionochloa defracta and Festuca ultramafica, two serpentine endemics. Cluster analysis showed that replicate samples of taxa were classified together in 70% of cases. Ordination of phytolith types identified a major gradient based on the presence/absence of panicoid and chloridoid types. A secondary gradient was related to the frequency of chionochloid, truncated cone, and other short‐cell phytoliths. Chionochloa taxa fall into 3 categories on the basis of the presence of panicoid (8 taxa) or chionochloid (11 taxa) phytolith types, or the absence of both (14 taxa). Species of Festuca had relatively high frequencies of points compared with Chionochloa, and absence or low frequency of dumbbell and chionochloid types. There was more interspecific variation among species of Chionochloa than in Festuca.

Satellite observation of Keppel Islands (Great Barrier Reef) 2002 coral bleaching using IKONOS data - Christopher D. Elvidge; John B. Dietz; Ray Berkelmans; Serge Andréfouët; William Skirving; Alan E. Strong; Benjamin T. Tuttle (Coral Reefs, 2004)

A comparison of the 1998 and 2002 coral bleaching events on the Great Barrier Reef: spatial correlation, patterns, and predictions - Ray Berkelmans; Glenn De’ath; Stuart Kininmonth; William J. Skirving (Coral Reefs, 2004)

Enhancement of Solubility and Bioavailability of β-Lapachone Using Cyclodextrin Inclusion Complexes - Norased Nasongkla; Andy F. Wiedmann; Andrew Bruening; Meghan Beman; Dale Ray; William G. Bornmann; David A. Boothman; Jinming Gao (Pharmaceutical Research, 2003)

Development of gypsy moth larvae feeding on red maple saplings at elevated CO 2 and temperature - Ray S. Williams; David E. Lincoln; Richard J. Norby (Oecologia, 2003)

Non-litter effects of elevated CO2 on forest floor microarthropod abundances - Randi A. Hansen; Ray S. Williams; David C. Degenhardt; David E. Lincoln (Plant and Soil, 2001)

Integrated commodity management methods with ca and/or fumigation - S. Prabhakaran; S. Ray; B. M. Schneider; R. E. Williams; P. Flinn; T. Phillips; D. Hagstrum; F. Arthur; J. Throne; R. N. Emery; R. A. Tassone; E. Kostas; et al. (Phytoparasitica, 2001)

Effects of elevated CO 2 and temperature‐grown red and sugar maple on gypsy moth performance - Ray S. Williams; Richard J. Norby; David E. Lincoln (Global Change Biology, 2000)
Summary Few studies have investigated how tree species grown under elevated CO 2 and elevated temperature alter the performance of leaf‐feeding insects. The indirect effects of an elevated CO 2 concentration and temperature on leaf phytochemistry, along with potential direct effects on insect growth and consumption, may independently or interactively affect insects. To investigate this, we bagged larvae of the gypsy moth on leaves of red and sugar maple growing in open‐top chambers in four CO 2 /temperature treatment combinations: (i) ambient temperature, ambient CO 2 ; (ii) ambient temperature, elevated CO 2 (+ 300 μL L −1 CO 2 ); (iii) elevated temperature (+ 3.5°C), ambient CO 2 ; and (iv) elevated temperature, elevated CO 2 . For both tree species, leaves grown at elevated CO 2 concentration were significantly reduced in leaf nitrogen concentration and increased in C: N ratio, while neither temperature nor its interaction with CO 2 concentration had any effect. Depending on the tree species, leaf water content declined (red maple) and carbon‐based phenolics increased (sugar maple) on plants grown in an enriched CO 2 atmosphere. The only observed effect of elevated temperature on leaf phytochemistry was a reduction in leaf water content of sugar maple leaves. Gypsy moth larval responses were dependent on tree species. Larvae feeding on elevated CO 2 ‐grown red maple leaves had reduced growth, while temperature had no effect on the growth or consumption of larvae. No significant effects of either temperature or CO 2 concentration were observed for larvae feeding on sugar maple leaves. Our data demonstrate strong effects of CO 2 enrichment on leaf phytochemical constituents important to folivorous insects, while an elevated temperature largely has little effect. We conclude that alterations in leaf chemistry due to an elevated CO 2 atmosphere are more important in this plant–folivorous insect system than either the direct short‐term effects of temperature on insect performance or its indirect effects on leaf chemistry.

Aquacultural Effluents: Directive Signals to the System Downstream? - Ray H. Kamps; William H. Neill (Journal of Chemical Ecology, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Movement-related potentials with reference to isometric force output in discrete and repetitive tasks - S. M. Slobounov; William J. Ray (Experimental Brain Research, 1998)

Cloning and tissue expression of the mouse ortholog of AIM1, a βγ-crystallin superfamily member - Ulrike Teichmann; Michael E. Ray; Jane Ellison; Caroline Graham; Graeme Wistow; Paul S. Meltzer; Jeffrey M. Trent; William J. Pavan (Mammalian Genome, 1998)

Leaf age effects of elevated CO 2 ‐grown white oak leaves on spring‐feeding lepidopterans - RaY. S. Williams; David E. Lincoln; Richard J. Norby (Global Change Biology, 1998)
Folivorous insect responses to elevated CO 2 ‐grown tree species may be complicated by phytochemical changes as leaves age. For example, young expanding leaves in tree species may be less affected by enriched CO 2 ‐alterations in leaf phytochemistry than older mature leaves due to shorter exposure times to elevated CO 2 atmospheres. This, in turn, could result in different effects on early vs. late instar larvae of herbivorous insects. To address this, seedlings of white oak ( Quercus alba L.), grown in open‐top chambers under ambient and elevated CO 2 , were fed to two important early spring feeding herbivores; gypsy moth ( Lymantria dispar L.), and forest tent caterpillar ( Malacosoma disstria Hübner). Young, expanding leaves were presented to early instar larvae, and older fully expanded or mature leaves to late instar larvae. Young leaves had significantly lower leaf nitrogen content and significantly higher total nonstructural carbohydrate:nitrogen ratio as plant CO 2 concentration rose, while nonstructural carbohydrates and total carbon‐based phenolics were unaffected by plant CO 2 treatment. These phytochemical changes contributed to a significant reduction in the growth rate of early instar gypsy moth larvae, while growth rates of forest tent caterpillar were unaffected. The differences in insect responses were attributed to an increase in the nitrogen utilization efficiency (NUE) of early instar forest tent caterpillar larvae feeding on elevated CO 2 ‐grown leaves, while early instar gypsy moth larval NUE remained unchanged among the treatments. Later instar larvae of both insect species experienced larger reductions in foliage quality on elevated CO 2 ‐grown leaves than earlier instars, as the carbohydrate:nitrogen ratio of leaves substantially increased. Despite this, neither insect species exhibited changes in growth or consumption rates between CO 2 treatments in the later instar. An increase in NUE was apparently responsible for offsetting reduced foliar nitrogen for the late instar larvae of both species.

Effects of elevated CO 2 ‐grown loblolly pine needles on the growth, consumption, development, and pupal weight of red‐headed pine sawfly larvae reared within open‐topped chambers - RAY WILLIAMS; DAVID LINCOLN; RICHARD THOMAS (Global Change Biology, 1997)
Seedlings of loblolly pine, Pinus taeda , were grown in open‐topped chambers under four levels of CO 2 : two ambient and two elevated. Larvae of the red‐headed pine sawfly, Neodiprion lecontei , were reared from early instar to pupation, primarily on branches within chambers. Larval growth and mortality were assessed and leaf phytochemistry samples of immature and mature leaves collected weekly. Mature leaves grown under elevated CO 2 had significant reductions in leaf nitrogen and increases in non‐structural carbohydrate contents, resulting in foliage being a poorer food source for larvae, i.e. higher carbohydrate:nitrogen ratio. Nutritional constituents of immature needles were unaffected by seedling CO 2 treatment. Volatile mono‐ and sesquiterpenes were unrelated to plant CO 2 treatments for either leaf age class. Larval consumption of immature needles significantly increased on seedlings grown under CO 2 enrichment, while mature needle consumption was not different between the treatments. The average weight gain per larva significantly declined in late instar larvae consuming elevated CO 2 ‐grown needles. In spite of this reduced growth, neither the days to pupation nor pupal weights were different among the CO 2 treatments. This study suggests that enriched CO 2 ‐induced alterations in pine needle phytochemistry can affect red‐headed pine sawfly performance. However, compensatory measures by larvae, such as choosing to consume more nutritious immature needles, apparently helps offset enriched CO 2 ‐induced reductions in the leaf quality of mature needles.

Predation of zebra mussels by round gobies, Neogobius melanostomus - William J. Ray; Lynda D. Corkum (Environmental Biology of Fishes, 1997)

Susceptibility of potato varieties and advanced breeding lines (Solanum tuberosum L.) toPhytophthora infestans (Mont.) de Bary in greenhouse screenings - David S. Douches; William W. Kirk; Kazimierz Jastrzebski; Christopher Long; Ray Hammerschmidt (American Journal of Potato Research, 1997)

Mechanical and biochemical analyses of tibial compartment fascia in chronic compartment syndrome - Christof Hurschler; Ray Vanderby; Daniel A. Martinez; Arthur C. Vailas; William D. Turnipseed (Annals of Biomedical Engineering, 1994)

Accumulation and persistence of picloram (Tordon 10K) in surface water and bottom sediments in West Virginia - D. Steve Dennis; William H. Gillespie; Robert A. Maxey; Ray Shaw (Archives of Environmental Contamination and Toxicology, 1977)